Exploratory Analysis of the Links among Food Consumption Profiles, Prenatal Androgens, and Selected Measures of Quality of Life - Modlinska, Klaudia; Pisula, Wojciech (Frontiers in Public Health, 2016)
Prenatal sex steroids play a vital role in the development of the whole organism, and therefore also the brain. Exposure of the fetus to testosterone seems to be of special importance both for typical development and pathology. The key factor impacting offspring development (including prenatal androgen levels) appears to be diet, both in terms of shortage and excessive intake of certain food products. Prenatal steroid levels are measured using the ratio of the lengths of the second and fourth fingers (2D:4D). So far the digit ratio (2D:4D) has been shown to correlate negatively with prenatal testosterone and positively with prenatal estrogen. Numerous correlational studies found relationships between the 2D:4D phenotype and differences in magnitude of many psychological traits. Certain social and demographic variables also correlate with the digit ratio. The present paper offers a preliminary analysis of correlations between diet, prenatal hormones' levels (established based on the digit ratio) and selected social variables. One of the findings is that countries with high meat consumption present the so-called masculine digit ratio, while countries with plant-based diets – a feminine digit ratio.